The Effect of Single-Leg Speed Hop Exercise on Leg Muscle of Aerobic Athletes - Gita Trisanda; Ni Putu Nita Wijayanti; Hirja Hidayat; Muhammad Fiqri (Journal of Coaching and Sports Science, 2022)
Power is indispensable for every sport that requires physical skills. Poor athlete's leg power will hinder optimal performance. This study aimed to determine the effect of single-leg speed on the leg muscle power of aerobic athletes. Experimental research was used as the research method. The tool used to analyze the data was the SPSS version 23. The sample consisted of eight participants. The research results after the pretest and posttest showed a significant effect of single leg speed hop exercise on the leg muscle power of Riau aerobics athletes, with tobserved of 14,333 and tcritical of 1,895 (significant level of 0,05). The conclusion from this study is that the single leg speed hop exercise positively impacts aerobic gymnast leg muscle strength.